"Dude I've Never Felt This Way Towards a Celebrity Death": Parasocial Grieving and the Collective Mourning of Kobe Bryant on Reddit. (December 2022) - Bingaman, James
Although research acknowledges the existence of parasocial relationships, if these relationships are possible then, inevitably, these relationships will dissolve. The emotions associated with parasocial breakups, especially that of grieving, are vital to understanding the totality of relationships between spectators and sports figures. After the devastating death of NBA legend Kobe Bryant, a content analysis was used to explore the emotional and mental responses of grief posted on Reddit. The results suggest that sadness and shock were the most common responses of grief across Reddit threads, while the use of reminiscing and memorializing was also prevalent across both. Additionally, this study provides evidence to support the notion that like real relationships, emotional responses of grief like sadness dissipate over time, while other emotional responses like love increase. Thus, any study examining parasocial grieving must do so longitudinally as parasocial grief, like real grief, is a process not momentary.